2010
DOI: 10.1002/jemt.20965
|View full text |Cite
|
Sign up to set email alerts
|

Compensation of inhomogeneous fluorescence signal distribution in 2D images acquired by confocal microscopy

Abstract: In images acquired by confocal laser scanning microscopy (CLSM), regions corresponding to the same concentration of fluorophores in the specimen should be mapped to the same grayscale levels. However, in practice, due to multiple distortion effects, CLSM images of even homogeneous specimen regions suffer from irregular brightness variations, e.g., darkening of image edges and lightening of the center. The effects are yet more pronounced in images of real biological specimens. A spatially varying grayscale map … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…To overcome the problem of light attenuation in images acquired by fluorescence microscopy, non-homogeneous fluorescent signal distribution is compensated for using Plane Brightness Adjustment, a plugin in the ImageJ software package [ 38 ]. Download ‘Plane_Brightness_Adjustment.jar’ from https://imagej.nih.gov/ij/plugins/plane-brightness/index.htm and drop the plugin into the plugins > Stack folder.…”
Section: Methodsmentioning
confidence: 99%
“…To overcome the problem of light attenuation in images acquired by fluorescence microscopy, non-homogeneous fluorescent signal distribution is compensated for using Plane Brightness Adjustment, a plugin in the ImageJ software package [ 38 ]. Download ‘Plane_Brightness_Adjustment.jar’ from https://imagej.nih.gov/ij/plugins/plane-brightness/index.htm and drop the plugin into the plugins > Stack folder.…”
Section: Methodsmentioning
confidence: 99%
“…Inhomogenous illumination, where different parts of the imaging field have different brightness intensities due to the microscope setup even though in the actual sample they are not variable, can prevent the alignment routines from working. This issue was addressed in Michálek et al (2010), where it was demonstrated how registration of overlaps in two neighboring fields of view whose brightness intensities decline from the center of the image to the edge may fail entirely. To solve this problem, Michálek et al (2010) proposed a fast algorithm capable of compensating slowly varying lateral brightness distribution, which, when applied before registration, can significantly improve registration results.…”
Section: Methodsmentioning
confidence: 99%
“…This issue was addressed in Michálek et al (2010), where it was demonstrated how registration of overlaps in two neighboring fields of view whose brightness intensities decline from the center of the image to the edge may fail entirely. To solve this problem, Michálek et al (2010) proposed a fast algorithm capable of compensating slowly varying lateral brightness distribution, which, when applied before registration, can significantly improve registration results. In the method in question, stacks of confocal images are processed without user intervention.…”
Section: Methodsmentioning
confidence: 99%
“…One of the most important properties of a matching method is the robustness, because a sufficient number of correct correspondences must be achieved, avoiding false matchings that could mislead the whole image registration stage. It is worth noting that the accuracy of the Feature Matching could be strongly influenced by the nonuniformity of the intensity inside each single image (Evangelidis & Psarakis, ; Michálek et al ., ). Warping Model Estimation . Once image correspondences are computed, they can be used to infer the warping transformations linking the different views.…”
Section: State Of the Artmentioning
confidence: 99%